Steroid-responsive proximal myopathy with dystrophic muscle biopsy in a young male: a diagnostic dilemma - Butt, Nauman Ismat; Ghoauri, Muhammad Sohail Ajmal (International Journal of Pathology, 2025)
Background: Limb Girdle Muscular Dystrophy Type 2B (LGMD2B) can closely mimic polymyositis, particularly in young adults and may show misleading short-term steroid responsiveness. However, unlike inflammatory myopathies, they do not benefit from long-term immunosuppression, which may in fact accelerate muscle degeneration. Case report: We report the case of a 21-year-old male presenting with acute-onset progressive proximal muscle weakness and markedly elevated creatine phosphokinase levels. The clinical picture, along with a transient response to corticosteroids, initially suggested inflammatory myopathy of polymyositis. However, muscle biopsy revealed dystrophic features with minimal inflammation and autoimmune serologies were negative, suggesting an underlying muscular dystrophy, specifically LGMD2B. Conclusion: This case underscores the importance of a comprehensive diagnostic approach in patients with proximal myopathy. Overreliance on steroid responsiveness or elevated CPK levels can lead to misdiagnosis. Differentiating muscular dystrophies from inflammatory myopathies is essential to avoid unnecessary immunosuppression.